Pengaruh Brand Image dan Promosi Terhadap Keputusan Pembelian Smartphone Vivo Di Erafone Parung Ciputat - Sepya Ananda Sahari; Aldila Rahma Putri (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of Brand Image and Promotion both partially and simultaneously on Vivo Smartphone Purchasing Decisions at Erafone Parung Ciputat. The method used is quantitative. The sampling technique used the slovin formula with a sample size of 188 respondents. Data collection by means of a questionnaire, and data analysis techniques with validity, reliability, classical assumption tests, simple regression analysis, multiple regression, t test hypothesis testing, f test, and coefficient of determination. The results of this study indicate that partially Brand Image has a significant effect on purchasing decisions. With tcount> t table (22.664> 1.972) From the results of simple linear regression analysis, the regression equation Y = 6.399 + 1.059X1 is obtained, the regression coefficient value of 0.747 shows a (positive) influence. and Promotion has a significant influence on Purchasing Decisions with tcount> t table (28.881> 1.972). And obtained the value of the regression equation Y = 6.805 + 1.039 X2. so, the regression coefficient of 0.904 shows a (positive) influence, while simultaneously Brand Image and Promotion have a significant effect on Purchasing Decisions with the regression equation Y = 4.766 + 0.338 X1 + 0.763 X2, showing a (positive) influence. And the results of the hypothesis test obtained the value fhitung> ftabel or (467.006> 3.04), while the coefficient of determination is 0.835, meaning that Brand Image and Promotion have a significant effect on purchasing decisions by 83.5%, while the remaining 16.5% is influenced by other factors.